Transformasi Produktivitas Melalui Komunikasi Digital Smartwacth - Mardani, Puri Bestari; Rut Rismanta; Christanti, Maria Febiana (FISIP UPNVJ, 2025)
Revolutionary changes within the field of information technology now directly impacts communication as well as individual productivity. This includes the latest innovations such as smartwatches that serve as a form of digital communication. In Indonesia, smartwatch adoption has reached 23.7% of Internet users and continues to grow. This indicates a tremendous potential to transform productivity approaches. The aim of the study is to examine the phenomenon of productivity shifts that occur when people use smartwatches through the lens of the Persuasive Technology Model. To gather insights and experiences of smartwatch users, Focus Group Discussions (FGDs) and in-depth interviews were conducted with participants across Indonesia. In this study, data analysis was conducted based on three key elements of the Persuasive Technology Model: motivation, ability, and trigger. The theoretical implications of the study suggest that the effectiveness of the Persuasive Technology Model motivates with multidimensional incentives as opposed to singular motivators. The model proves that strategies designed in information-based progressive technologies facilitate increased engagement through digital communication, which incrementally enhances the capabilities and benefits accessible to the users. Considering Indonesia’s culture of collectivism, the more social factors concerning culture than technology have starker impacts on adoption trends of wearable technology. Automation and manual intervention both play a role in upholding a user’s feeling of urgency.